A Review of Hematoma Components Clearance Mechanism After Subarachnoid Hemorrhage - Pan, Pengjie; Xu, Li; Zhang, Hongrong; Liu, Yuan; Lu, Xiaocheng; Chen, Gang; Tang, Hailiang; Wu, Jiang (Frontiers in Neuroscience, 2020)
Subarachnoid hemorrhage (SAH) is a complicated clinical syndrome, which is caused by several kinds of cerebrovascular disorders, with high morbidity, disability and mortality rate. In recent years, several studies have shown that early brain injury (EBI) is an important factor leading to the poor prognosis of SAH. A major cause of EBI has been attributed that hematoma components invade into the brain parenchyma, resulting in neuronal cell death. Therefore, the clearance of hematoma components is essential in the clinical outcome of patients after SAH. Here, in the review, we provide a summary of the current known hematoma components clearance mechanisms and simultaneously propose a new hypothesis for hematoma components clearance.